PERAN PENGAWASAN MASYARAKAT TERHADAP PENGELOLAAN KEUANGAN DESA DALAM MEWUJUDKAN AKUNTABILITAS KEUANGAN DI DESA - Mohammad Herli; Hafidhah , (Fakultas Ekonomi dan Bisnis, 2017)
The community's active role in monitoring village financial management is still weak. Many cases of village misconduct by village administrations are caused by a lack of community control over village finances. There are several factors causing the lack of participation of villagers in the supervision of the lack of public communication space in the village so that people do not know how to conduct supervision of the village administration. Community supervision can be conducted directly or indirectly and the implementation of supervision can be done before, during, and after activity pelakasanaan. Monitoring prior to implementation is done through community involvement in village financial planning, supervision during activities can be undertaken by the community by monitoring the development and management of village finances by village governance, while supervision after the activities can be done by monitoring the results of the implementation of development in the village. Keywords : Supervision, Society, Finance, Village